Development of a smart reconfigurable reflector prototype for an extremely high-frequency antenna. (April 2016) - Hiroaki, Tanaka; Sakamoto, Hiraku; Inagaki, Akiya; Ishimura, Kosei; Doi, Akihiro; Kono, Yusuke; Oyama, Tomoaki; Watanabe, Kazuki; Oikawa, Yu; Kuratomi, Takeshi
A prototype for a space-borne smart reconfigurable reflector, whose reflector surface can be changed intentionally using surface adjustment actuators, has been developed, and its performance was evaluated through experiments. The smart reconfigurable reflector was designed as a sub-reflector of a space antenna for observations in the extremely highfrequency band (frequency range: 30 -300 GHz) and is used for correcting the path length errors in the antenna system caused by surface deformations of the main reflector. It consists of a solid surface, supporting members, and surface adjustment actuators. The surface adjustment actuators are a key part of the smart reconfigurable reflector, and each consists of a piezoelectric stack actuator and a displacement magnifying mechanism. Functional tests were performed in order to investigate the performance of the actuator. The results indicate that the actuator has a stroke of more than 0.9 mm with an accuracy of 0.01 mm and a force of more than 90 N. The control accuracy was much better than the required surface accuracy for an extremely high-frequency antenna system. The effectiveness of the developed reflector system was demonstrated through numerical simulations and shape modification experiments. In order to clarify the effectiveness of the developed smart reconfigurable reflector, the performance of the antenna system, equipped with the smart reconfigurable reflector, was evaluated. The experimental results confirmed the performance expected from the numerical simulation and indicated that the antenna could be adequately controlled as expected.